1997
DOI: 10.1038/bjc.1997.569
|View full text |Cite
|
Sign up to set email alerts
|

Circulating soluble adhesion molecules E-cadherin, E-selectin, intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) in patients with gastric cancer

Abstract: Summary The concentrations of the soluble adhesion molecules E-cadherin, E-selectin, intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) were investigated in 45 patients with gastric cancer before treatment and their correlation with clinical, histological and routine laboratory parameters was examined. Data were collected on tumour stage at presentation, presence and sites of metastatic disease, tumour pathology, survival and results of routine laboratory tests. Serum con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 42 publications
3
23
0
1
Order By: Relevance
“…Our results extend these observations for patients with colorectal cancer and for the first time report elevated serum concentrations of VCAM-1 in colorectal cancer. This finding is in keeping with our previous observations of elevated VCAM-1 in patients with different gastrointestinal cancers and with gastric cancer, in particular, in which VCAM-1 concentrations seems to have independent prognostic significance (Banks et al, 1993;Velikova et al, 1997).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results extend these observations for patients with colorectal cancer and for the first time report elevated serum concentrations of VCAM-1 in colorectal cancer. This finding is in keeping with our previous observations of elevated VCAM-1 in patients with different gastrointestinal cancers and with gastric cancer, in particular, in which VCAM-1 concentrations seems to have independent prognostic significance (Banks et al, 1993;Velikova et al, 1997).…”
Section: Discussionsupporting
confidence: 93%
“…After observations of a strong correlation of circulating ICAM-1, VCAM-1, E-cadherin and E-selectin with serum alkaline phosphatase in patients with gastric cancer, we have suggested that soluble adhesion molecules might have a biliary route of excretion and their clearance might be impaired in the presence of intrahepatic cholestasis secondary to liver metastases (Velikova et al, 1997). In the colorectal cancer patients, the correlation between some soluble adhesion molecules and serum alkaline phosphatase is still present but not as strongly as in the gastric cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 This suggests that adhesion proteins can be released or shed, as opposed to exclusively being expressed on the cell surface after synthesis. We assayed the supernatant from these cells using either ELISA techniques or Western blotting.…”
Section: Icam-1 and Vcam-1 Proteins Are Present And Expressed On The mentioning
confidence: 99%
“…VCAM-1 expression is prevalent in areas of neovascularization and inflammatory infiltrate in atherosclerotic plaques (11). A soluble form of VCAM-1 is known to be shed from VCAM-1 on the cell surface and up-regulated in some diseases, including chronic inflammatory diseases (12) and some cancers (13,14). Soluble VCAM-1 (sVCAM-1) 3 has also been reported to exhibit angiogenic activity in vivo through mediating endothelial cell chemotaxis activity (15).…”
mentioning
confidence: 99%